Influence of concentration and type of support material on the immobilization of Oenococcus oeni - Genisheva, Zlatina Asenova (2011)
The malolactic fermentation (MLF) in winemaking is a complex and difficult to control biological process . The implementation of MLF is very important for wines produced in cold regions as it reduces the acidity, brings biological stability and may improve the organolept ic characteristics of the product. MLF normally occurs spontaneously during storage of a new wine and is usually a very slow process that can undergo for we eks and even months, and not always give a satisfactory result. The use of immobilized lactic acid bacteria during MLF helps to accelerate the process and also simplifies the control of its extension. However, t he material to be used as immobilization support must be carefully chosen in order to not negatively affect the final product, and should also be cheap, abundant i n nature, and of food grade purity. The aim of the present work was to evaluate differe nt low cost natural materials of food grade purity (na mely corn cobs, grape stems and grape skins) and their concentration, for immobilization of Oenococcus oeni for use on MLF.